Determining Classroom Teachers' Attitudes Towards Artificial Intelligence - Aksakal, Şeyma; Emre, İrfan; Özbek, Mehmet (Ahmet DURMAZ, 2024)
In this study, it was aimed to determine the attitudes of classroom teachers towards artificial intelligence. The sample of the study, which was conducted with the survey model, consists of 308 classroom teachers working in primary schools in Elazığ city center in 2023-2024. The scale, which consists of two sub-dimensions as positive and negative attitudes, has a 5-point Likert structure and consists of 20 items. After examining the normality distribution of the data obtained, the data were analyzed with MANOVA test using SPSS 21.0 statistical program. It was observed that the classroom teachers who participated in the study responded to the positive attitude sub-dimension at the level of "Agree" (X=3,71±1,04), and to the items in the negative sub-dimension at the level of "Disagree" (X=2,74±,97). In the study, the differences between the groups in terms of gender, educational status, professional seniority, graduated school, and age variables were investigated and it was seen that there was a significant difference in favor of male and female teachers in the negative attitude sub-dimension in the results of MANOVA analysis only in the gender variable.

Bu araştırmada sınıf öğretmenlerinin yapay zekaya ilişkin tutumlarının belirlenmesi amaçlanmıştır. Tarama modeli ile yürütülen çalışmanın örneklemini 2023-2024 yılında Elazığ il merkezinde bulunan ilkokullarda görev yapan 308 sınıf öğretmeni oluşturmaktadır. Pozitif ve negatif tutum olmak üzere iki alt boyuttan oluşan ölçek 5’li Likert yapıdadır ve 20 maddeden oluşmaktadır. Elde edilen verilerin normallik dağılımları incelendikten sonra SPSS 21.0 istatistik programı kullanılarak veriler MANOVA testi ile analiz edilmişlerdir. Araştırmaya katılan sınıf öğretmenlerinin pozitif tutum alt boyutuna “Katılıyorum” (X=3,71±1,04) düzeyinde, negatif alt boyuttaki maddelere ise “Katılmıyorum” (X=2,74±,97) düzeyinde cevap verdikleri görülmüştür. Araştırmada cinsiyet, eğitim durumu, mesleki kıdem, mezun olunan okul, yaş değişkenleri açısından gruplar arasındaki farklar araştırılmış ve sadece cinsiyet değişkeninde MANOVA analizi sonuçlarında negatif tutum alt boyutunda kadın ve erkek öğretmenler açısından erkek öğretmenler lehine anlamlı bir farkın oluştuğu görülmüştür.
Sınıf Öğretmenlerinin Yapay Zekaya İlişkin Tutumlarının Belirlenmesi
Keywords: Teacher Education and Professional Development of Educators; Öğretmen Eğitimi ve Eğitimcilerin Mesleki Gelişimi; Other Fields of Education (Other); Alan Eğitimleri (Diğer); Specialist Studies in Education (Other); Eğitim Üzerine Çalışmalar (Diğer)